Rapid alteration of serum interleukin‐6 levels may predict the reactivity of i.v. cyclophosphamide pulse therapy in systemic sclerosis‐associated interstitial lung disease. Issue 10 (27th July 2018) - Numajiri, Hiroko; Yoshizaki, Ayumi; Fukasawa, Takemichi; Ebata, Satoshi; Nakamura, Kouki; Yamashita, Takashi; Saigusa, Ryosuke; Miura, Syunsuke; Hirabayashi, Megumi; Yoshizaki, Asako; Sumida, Hayakazu; Asano, Yoshihide; et al.
Abstract: Systemic sclerosis (SSc) is an autoimmune disorder characterized by excessive extracellular matrix deposition. Although SSc‐associated interstitial lung disease (ILD) is one of the most important complications as a cause of death in SSc, prediction factors of treatment reactivity in SSc‐ILD are still unclear. To assess relationships between interleukin (IL)‐6 and reactivity to treatment, we measured serum IL‐6 levels in 23 of active SSc‐ILD patients under i.v. cyclophosphamide (IVCY) therapy and 20 of stabilized SSc‐ILD, using the high‐sensitivity enzyme‐linked immunoassay system. Serum IL‐6 levels in active SSc‐ILD patients were significantly higher than those in stabilized SSc‐ILD patients. Among active SSc‐ILD patients, baseline serum IL‐6 levels were not significantly different between IVCY responders and non‐responders. Meanwhile, serum IL‐6 levels after three IVCY doses out of a total of six were decreased in responders but not in non‐responders. Regarding changes of parameters by the three doses of a total of six of IVCY, change in serum IL‐6 levels correlated inversely with that in values of pulmonary function test. Thus, the rapid decrease in serum IL‐6 levels during a couple of doses may predict the efficacy of IVCY therapy against SSc‐ILD.